Abnormal glycemic homeostasis at the onset of serious mental illnesses: A common pathway. (May 2016) - Garcia-Rizo, Clemente; Kirkpatrick, Brian; Fernandez-Egea, Emilio; Oliveira, Cristina; Bernardo, Miquel
Highlights: Patients with serious mental illnesses present an abnormal glycemic state at onset. A pre-diabetic state might explain the increased morbidity and mortality over time. A theoretical explanation relies on the high prevalence of obstetric complications. Early life stressful events would predict metabolic disturbances ongoing at onset. Abstract: Objective: Patients with serious mental illnesses exhibit a reduced lifespan compared with the general population, a finding that can not solely rely on high suicide risk, low access to medical care and unhealthy lifestyle. The main causes of death are medical related pathologies such as type 2 diabetes mellitus and cardiovascular disease; however pharmacological treatment might play a role. Material and methods: We compared a two hour glucose load in naïve patients at the onset of a serious mental illness ( N  = 102) (84 patients with a first episode of schizophrenia and related disorders, 6 with a first episode of bipolar I disorder and 12 with a first episode of major depression disorder) with another psychiatric diagnose, adjustment disorder ( N  = 17) and matched controls ( N  = 98). Results: Young patients with serious mental illness showed an increased two hour glucose load compared with adjustment disorder and the control group. Mean two hour glucose values [±standard deviation] were: for schizophrenia and related disorders 106.51 mg/dL [±32.0], for bipolar disorder 118.33 mg/dL [±34.3], for major depressive disorder 107.42 mg/dL [±34.5], for adjustment disorder 79.06 mg/dL[±24.4] and for the control group 82.11 mg/dL [±23.3] ( p  < 0.001). Conclusions: Our results reflect an abnormal metabolic pathway at the onset of the disease before any pharmacological treatment or other confounding factors might have taken place. Our results suggest a similar glycemic pathway in serious mental illnesses and the subsequent need of primary and secondary prevention strategies.